The Low Incidence of Viral Hepatitis Reactivation Among Subjects on Immunotherapy Reduces the Impact of Suboptimal Screening Rate - Aceituno, Laia; Bañares, Juan; Ruiz-Ortega, Lourdes; Callejo-Pérez, Ana; Muñoz-Couselo, Eva; Ortiz-Velez, Carolina; Díaz-Mejía, Nely; Barreira-Díaz, Ana; Carreras, María José; Farriols, Anna; Buti, María; Riveiro-Barciela, Mar (Frontiers in Medicine, 2022)
Background and aims: immunotherapy with immune checkpoint inhibitors (ICIs) is a pillar of many advanced tumours. However, there is scarce data concerning the rate of viral hepatitis screening on this population or the risk of viral reactivation. Methods: retrospective-prospective study that includes all patients who began ICIs between January/2019 and December/2020 in a University Hospital. Data on viral hepatitis screening prior to the beginning of ICIs were collected. In subjects lacking information, serological tests were requested prospectively. Among HBsAg, anti-HBc or anti-HCV positive subjects, reactivation was prospectively assessed. Results: during the 2-year period of study 595 subjects received ICIs (61.2% male, mean age 63 years). The most prevalent cancers found were 35.5% lung cancer, 12.1% melanoma, 8.2% head and neck; ICIs schemes were mainly anti-PD1 (65.7%), followed by anti-PD-L1 (19.2%), and combined therapy (13.6%). Prior to immunotherapy anti-HCV screening was performed in 462 (77.6%) subjects, HBsAg in 462 (77.6%), anti-HBc in 335 (56.3%) and the complete screening in 328 (55.1%). Anti-HBc screening was more frequently ordered among patients treated with concomitant systemic therapy (p=0.003), especially in case of chemotherapy (p=0.015), though HCV screening was more commonly performed in concomitant therapies different to chemotherapy (p=0.001). Serological tests were completed prospectively in those alive, leading to an overall prevalence for anti-HCV of 3.5%, HBsAg 1.3% and anti-HBc 15.2%. HCV-RNA was detected in 2/19 (both patients with hepatocellular carcinoma), HBV-DNA in 4/7 HBsAg positive and in 1/75 anti-HBc positive subject. Five out of the 7 HBsAg carriers and 1/75 anti-HBc+ subjects (due to concomitant antiretroviral therapy) received antiviral prophylaxis. Neither cases of HBV reactivation nor changes in HCV viral load were observed. Discussion: HBV and HCV screening prior to immunotherapy is suboptimal. Though the rate of viral hepatitis reactivation seems extremely low, efforts should be made to optimize viral hepatitis screening prior to immunotherapy for selection of candidates for either antiviral prophylaxis or periodical follow-up.